Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Pada Instalasi Rawat Inap Rumah Sakit Umum Daerah Pandega Pangandaran - Ganjar Iskandar; Apri Budianto; Aini Kusniawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Overall patient satisfaction at the Pandega Hospital Inpatient Installation, Pangandaran Regency may be considered less than optimal in terms of suitability and consistency. Concerns regarding appropriateness arise from the lack of services provided by physicians and nurses in a timely and consistent manner. In particular, nurses were not adept at adequately explaining the necessary steps to patients. The level of patient satisfaction is influenced by the standard of service provided, and it is proven that Pandega Pangandaran Regional Hospital is still lagging behind in terms of reliability and responsiveness. The reliability of nurses is still lacking in providing comprehensive, thorough and fast services in accordance with the timeframe and responsiveness that has been determined, with nurses showing reluctance to handle patient complaints. This research was conducted using an explanatory survey method with quantitative methodology. The data analysis methodology used includes instrument testing to assess validity and reliability, research model testing using the coefficient of determination, and hypothesis testing using the t-test. The research results show that the level of service provided at the Pandega Pangandaran Hospital Inpatient Installation is of a high standard. Has the highest score on the empathy indicator and the lowest score on the responsiveness indicator. The level of patient satisfaction at the Pandega Pangandaran Hospital Inpatient Installation is quite high. Has the highest score on the aesthetic indicator and the lowest score on the suitability indicator. The research results found that service quality has a strong and beneficial influence on patient satisfaction at the Inpatient Installation of Pandega Pangandaran Regional Hospital. Thus, there is a direct relationship between the level of excellent service and patient satisfaction at the Pandega Pangandaran Hospital Inpatient Installation.